Master key generation to avoid the use of an external reference wave in an experimental JTC encrypting architecture (2012)
ABSTRACT: In experimental optodigital encrypting architectures, the use of a reference wave is essential. In this contribution, we present an experimental alternative to avoid the reference wave during the encrypting procedure in a joint transform correlator architecture by introducing the concept of a master key. Besides, the master key represents an additional security element for the entire protocol. In our method, the master key is holographically processed and used during the encryption process with the encrypting key. We give the mathematical description for the process in case of a single input object and then we extend it to multiple input objects. We present the experimental demonstration of the proposed method including two examples where this technique is successfully applied for several input objects.